Prevention and management of physical health conditions in adults with severe mental disorders: WHO recommendations - Petra C. Gronholm; Neerja Chowdhary; Corrado Barbui; Jayati Das-Munshi; Kavitha Kolappa; Graham Thornicroft; Maya Semrau; Tarun Dua (International Journal of Mental Health Systems, 2021)
Abstract Background People with severe mental disorders (SMD) experience premature mortality mostly from preventable physical causes. The World Health Organization (WHO) have recently produced guidelines on the prevention and management of physical health conditions in SMD. This paper presents the evidence which led to the recommendations presented in the guidelines. Methods The work followed the methodological principles for WHO guideline development. Systematic reviews in relation to the treatment of seven key priority physical health conditions and associated risk factors in persons with SMD were systematically sourced. The quality of this evidence was assessed, and compiled into evidence profiles. Existing guidelines and treatment recommendations were also considered. Based on this information, specific recommendations were developed on the prevention and management of physical health conditions and their risk factors amongst people with SMD. Results Nineteen recommendations were made in relation to the seven key priority physical health conditions and risk factors, alongside best practice statements for each condition. A mixture of conditional and strong recommendations were made, the quality of evidence underpinning these was generally low or very low. This is owing to the dearth of direct evidence relating to people living with SMD and comorbidities. Conclusions This paper presents evidence-based recommendations to prevent and manage physical health conditions in people with SMD. The recommendations are designed to inform policy makers, healthcare providers as well as other stakeholders about what they can do to improve the management of physical health conditions in adults with SMD and support the promotion of individual health behaviors to reduce the risk factors for these conditions. If implemented, these recommendations can improve the care that people with SMD receive for their physical health conditions in an equitable and person-centered manner, so that in future in relation to premature mortality ‘no-one is left behind’.